Plasma Levels of Receptor Interacting Protein Kinase-3 (RIP3), an Essential Mediator of Necroptosis, are Associated with Acute Kidney Injury in Critically Ill Trauma Patients. Issue 2 (August 2016) - Shashaty, Michael G.S.; Reilly, John P.; Sims, Carrie A.; Holena, Daniel N.; Qing, Danielle; Forker, Caitlin M.; Hotz, Meghan J.; Meyer, Nuala J.; Lanken, Paul N.; Feldman, Harold I.; Christie, Jason D.; Mangalmurti, Nilam S.
ABSTRACT: Background: Receptor interacting protein kinase-3 (RIP3) is a key mediator of necroptosis, a form of regulated cell death recently implicated in murine models of renal ischemia-reperfusion injury and transfusion-associated endothelial injury. The importance of necroptosis in human AKI is unknown. We hypothesized that plasma RIP3 concentrations would be associated with acute kidney injury (AKI) after severe trauma. Methods: We performed a case-control study nested in a prospective cohort of critically ill trauma patients. AKI was defined by AKI Network creatinine criteria within 6 days of presentation. Of 158 cohort subjects, we selected 13 who developed AKI stage 2 or 3, 27 with AKI stage 1, and 40 without AKI. We compared plasma RIP3 concentrations across these groups at presentation and 48 h. Since red blood cell (RBC) transfusion is an AKI risk factor, we also tested the association of RBCs transfused during resuscitation with RIP3 levels. Results: Median plasma RIP3 concentration rose more than 10-fold from presentation (15.6 (interquartile range 15.6–41.3) pg/mL) to 48 h (164.7 (66.9–300.6) pg/mL; P <0.001). RIP3 concentrations at 48 h were associated with AKI stage (no AKI: 144.8 (58.6–234.9) pg/mL; AKI stage 1: 165.8 (43.0–310.9) pg/mL; AKI stage 2–3: 365.5 (155.1–727.5) pg/mL; P = 0.010) whereas this association was not seen at presentation ( P = 0.324). RBC transfusions were also associated with 48-h plasma RIP3 (no RBCs: 99.4 (15.6–166.1) pg/mL; 1–5 units: 182.6 (98.5–274.1) pg/mL; >5 units: 341.8 (150.1–423.8) pg/mL; P <0.001). Conclusions: In critically ill trauma patients, plasma levels of the necroptosis mediator RIP3 at 48 h were associated with AKI stage and RBC transfusions.